The importance of Neuronutrition in the development of childhood Attention Deficit Disorder (ADHD): A literature review (Research, Society and Development, 2023)
Attention Deficit Hyperactivity Disorder is a neurobehavioral disorder, which presents symptoms of lack of concentration, impulsivity and/or intense agitation. The aim of this article is to investigate the eating behavior of children with ADHD, exploring the effects of nutrition as two factors that may contribute to the pathology and correlating studies on neuronutrition, vitamins and minerals such as vitamin D, essential fatty acids and minerals such as zinc and iron. The work is a qualitative narrative review of books, scientific articles and theses available on websites such as PubMed, Scopus and Google Scholar, Scielo, Digital Library of Theses and Dissertations of USP and LILACS. It is concluded that the daily intake of an adequate diet with ideal levels of vitamins and minerals is a condition capable of helping to treat ADHD, however, at this point, more corroborative studies are needed to confirm this.